2020
DOI: 10.3390/healthcare8040504
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the Polish Society of Diabetology and the Lifestyle of Patients with Type 2 Diabetes Mellitus: An Own Research

Abstract: Background and Objectives:Currently, diabetes is becoming a very serious challenge in medicine;type 2 diabetes mellitus (T2DM) is referred to as a noncontagious epidemic of the 21st century. The aim of the study is to assess the lifestyle of patients with type 2 diabetes, in particular eating habits, physical activity, and tobacco smoking, and to compare the obtained values with the latest recommendations of the Polish Society of Diabetology. Materials and Methods: The study group was comprised of 460 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…Notably, 70% of patients achieved the recommended intake of MUFA, followed by protein and PUFA consumption, while greater deviations were observed with respect to salt, saturated fatty acids, and carbohydrates. This study contrasts with the previously mentioned study, in which adherence to 7 out of 10 recommendations was reported [8]. Our observations may result, at least to some extent, from subjects following outdated diabetes dietary recommendations.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Notably, 70% of patients achieved the recommended intake of MUFA, followed by protein and PUFA consumption, while greater deviations were observed with respect to salt, saturated fatty acids, and carbohydrates. This study contrasts with the previously mentioned study, in which adherence to 7 out of 10 recommendations was reported [8]. Our observations may result, at least to some extent, from subjects following outdated diabetes dietary recommendations.…”
Section: Discussioncontrasting
confidence: 99%
“…Notwithstanding this heightened awareness, however, the nutritional composition of the reported food among these individuals did not manifest any substantial disparities when juxtaposed with the comparison group. This study's reported food intake composition closely resembled the type 2 diabetes patient's dietary survey by the Polish Society of Diabetology [8]. However, some discrepancies were noted between studies.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Institute Share research internationally facilitates education, cooperation, and problem-solving worldwide. Collaborations allow businesses and nations to pool resources, increase their knowledge, and spark new ideas 8 . The research raises the profile of a country in the eyes of the general public and the academic community.…”
Section: Introductionmentioning
confidence: 99%